If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3n + -5) = (9n + 8) + 5 Reorder the terms: 6(-5 + 3n) = (9n + 8) + 5 (-5 * 6 + 3n * 6) = (9n + 8) + 5 (-30 + 18n) = (9n + 8) + 5 Reorder the terms: -30 + 18n = (8 + 9n) + 5 Remove parenthesis around (8 + 9n) -30 + 18n = 8 + 9n + 5 Reorder the terms: -30 + 18n = 8 + 5 + 9n Combine like terms: 8 + 5 = 13 -30 + 18n = 13 + 9n Solving -30 + 18n = 13 + 9n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9n' to each side of the equation. -30 + 18n + -9n = 13 + 9n + -9n Combine like terms: 18n + -9n = 9n -30 + 9n = 13 + 9n + -9n Combine like terms: 9n + -9n = 0 -30 + 9n = 13 + 0 -30 + 9n = 13 Add '30' to each side of the equation. -30 + 30 + 9n = 13 + 30 Combine like terms: -30 + 30 = 0 0 + 9n = 13 + 30 9n = 13 + 30 Combine like terms: 13 + 30 = 43 9n = 43 Divide each side by '9'. n = 4.777777778 Simplifying n = 4.777777778
| ax+2=aw | | 4=t-5s | | 5n-8=-48 | | (x^3+4x^2)-(2x-8)=0 | | 3n-9=-27 | | 3-6(4+8n)=-21+10n | | 20r^2-41r+20=0 | | x(10x+24)=0 | | (s+16)(s+81)=0 | | 7-3x=15+5x | | 3-6(4+8n)=21+10n | | c(c+3)=0 | | y-(2y-5)=94 | | (3s+7)(s+6)=0 | | (3)-(-4)= | | s^2+11s+24=0 | | c^2-11c+18=0 | | 4x-7=3.5 | | -4(t+2)=12 | | s^7-7s=0 | | 32-14=3(x-4) | | -29+7x=-5(1-2x) | | 12x=6x+24 | | 12x=5x+24 | | 8y+2-6y=3+t-10 | | 5(3x-1)-3=25+4x | | z+2z= | | 12+3= | | -3x-8(1+x)=-2x+37 | | -9p(-6p+2)=-2p-9 | | 5(3z+7)=125 | | 1=12x^2+11x |